The Relationship Between Economic Development To Poverty In Indonesia - Rico Ferdian Pratama; Dedy Yuliawan (CV. ITTC INDONESIA, 2026)
Poverty remains one of the major challenges in economic development, particularly in developing countries such as Indonesia. Despite consistent economic growth, poverty reduction does not always occur proportionally, indicating the need to examine structural factors influencing poverty. This study aims to analyze the relationship between economic development represented by education, unemployment, and industrialization to poverty in Indonesia in both the short and long term. The research employs a quantitative approach using annual time series data from 1995–2024 obtained from the World Bank and the Central Bureau of Statistics (BPS). The analysis method applied is the Autoregressive Distributed Lag (ARDL) model to examine both short-term dynamics and long-term equilibrium relationships between variables. The results indicate that in the short term, education has a negative and significant effect on poverty in the current period, while unemployment significantly increases poverty in lag periods. Industrialization shows mixed effects, where it initially increases poverty but subsequently contributes to poverty reduction in later periods. In the long term, education and unemployment show negative but insignificant effects on poverty, whereas industrialization has a positive and significant effect. These findings suggest that economic development variables influence poverty dynamics, but the effectiveness of poverty reduction depends on the quality of education, labor market absorption, and the inclusiveness of industrial development.